(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2013)
Aim and objectives: The aim of this study was to evaluate the spectrum of breast diseases in the children and adolescents in a single hospital and to evaluate the presentation and outcome of these diseases. Methods: This prospective study of childhood and adolescents (2-19years) breast diseases conducted on 47 patients over a period from January 2009 to December 2011. A total of 47 (forty seven) children and adolescents (<19yrs) who complained of a breast lump or pain or nipple symptoms were included for the study. History, clinical examination along with breast ultrasound imaging and cytology and/ or biopsy in some cases was done for diagnosis. Patients were categorized according to their clinical properties and inflammatory, benign and malignant cases were done necessary operations. Other lesions was on medical treatment and under observation and follow-up. Results: The commonest complain was lump followed by pain. Most patients present in the age group 16-19 years (87%). The commonest breast lesion was fibroadenoma(36%). Most of them occur in 16-19 years age group (29.7%). Fibrocystic disease (8.4%) and breast abscess(8.4%) are next 2 common diseases. Diagnostic approach is mostly conservative with ultrasonogram. Few cases need FNAC and excision biopsy. Secondary malignancy may be a possible diagnosis. Awareness is essential for early diagnosis and treatment. DOI: http://dx.doi.org/10.3329/jpsb.v2i1.15157 Journal of Paediatric Surgeons of Bangladesh (2011) Vol. 2 (1): 12-16